Critical provincial transmission sectors for carbon dioxide emissions in China. (October 2021) - Wen, Wen; Feng, Cuiyang; Zhou, Hao; Zhang, Li; Wu, Xiaohui; Qi, Jianchuan; Yang, Xuechun; Liang, Yuhan
Abstract: The identification of critical sectors at the provincial level is important for achieving China's CO2 mitigation target. Previous studies have mainly adopted production-based or consumption-based methods to identify critical sectors on two sides of the supply chain. Some sectors located in the intermediate parts of the supply chains are commonly ignored but are critical transmission centers for CO2 emissions. In this study, we use a betweenness-based method based on multi-regional input-output tables to identify critical provincial transmission sectors for CO2 emissions in China in 2007, 2010, 2012, and 2015. The results show that some critical provincial transmission sectors are overlooked by production-based or consumption-based methods but transmit vast amounts of CO2 emissions in the intermediate supply chains, such as the Metal products in Hebei, and the Smelting and pressing of ferrous and nonferrous metals in Gansu. Moreover, critical provincial transmission sectors vary among different provinces and exhibit different patterns in different years. Most critical provincial transmission sectors were located in the northern, central and eastern coastal regions in 2007 and 2010, then shifted to the western region in 2012. In 2015, these sectors were mainly located in the central and eastern coastal regions. Analyzing the spatiotemporal variations in critical provincial transmission sectors can contribute to region-specific policy formulation for CO2 emission mitigation. Improving the intermediate input efficiency may also contribute to CO2 emission mitigation, such as tax breaks or subsidies in critical provincial transmission sectors. It is important to consider betweenness-based results as a complement to policy decisions. Highlights: Betweenness-based method is adopted to identify critical provincial transmission sectors for carbon dioxide emissions. Critical provincial sectors selected by three methods displayed different patterns. Improving the intermediate input efficiency may contribute to CO2 mitigation. Betweenness-based results complement critical provincial carbon dioxide emission mitigation policy.